Influência dos treinos do vocabulário expressivo e da consciência silábica no desenvolvimento inicial da leitura - Samantha Pereira (2018)
Researchs indicate that syllabic and phonemic manipulation (phonological awareness skills) influence the performance of children listeners, in the decoding of words in reading. Vocabulary also seems to play an important role in reading acquisition, although there is no consensus on its direct or indirect influence. Despite the apparent consensus in the literature, were not found studies that directly compared the influence of these repertoires in the initial reading learning. The main objective of this study was to verify if the abilities of expressive vocabulary and syllabic awareness influences the initial reading learning and to verify if one between the two abilities is preponderant. For this, 18 children, with 5 years and 5 months in average, students from a Municipal Infant Education Unit of Belo Horizonte, were divided into three homogeneous groups: GV, who trained vocabulary and reading; GS, who trained syllabic awareness and reading; and GC, who did not training anything. Evaluations of the vocabulary, phonological awareness and reading of canonical dissyllable words, isolated canonical syllables and letter naming were carried out with all groups at three different moments: at the beginning of the study; after the vocabulary and syllabic awareness training to GV and GS, and after the number of days equivalent to such trainings to the GC; and at the end of the study. The results showed that GS presented better performance than GV and GC in the second and third phonological awareness assessment. The difference between GV and GS in the vocabulary assessment was small, and the GC performed was a little smaller than the other groups. The reading training was effective for GV and GS, and GS showed better performance in the trained words and generalization (untrained words) reading. The GC did not show significant improvement in the words and syllables reading. Therefore, the data indicate that syllabic awareness training seems to favor the first words reading learning, so that would be interesting this type of training in basic education.